Human herpesvirus 8 infection contributes to a T helper 2 immune response in men from Tobago with prostate cancer. (12th October 2016) - Henning, Jill D; Bonachea, Luis A; Bunker, Clareann H; Patrick, Alan L; Jenkins, Frank J
Abstract : Objectives: To compare the cytokine profile between human herpesvirus 8 seropositive and seronegative men with and without prostate cancer. Methods: The study sample was obtained from the Tobago Prostate Survey, an ongoing study of prostate cancer in the Caribbean island of Tobago. Participants in the study were recruited mostly by public service announcement and by word of mouth. For analyses of circulating levels of pro‐inflammatory cytokines, participants with biopsy‐confirmed prostate cancer ( n = 79) were compared with control participants ( n = 87). Results: Cytokine analyses showed a T helper 2 response with suppressed T helper 1 response in prostate cancer patients, as evidenced by significantly increased levels of interleukin‐13 and reduced levels of interleukin‐12p70. Herpesvirus 8 seropositive men showed significantly increased levels of interleukin‐13 and interleukin‐10. At logistic regression analyses, interleukin‐12p70 predicted prostate cancer in 94.4% of human herpesvirus 8 seropositive men. Conclusions: These findings show that prostate cancer elicits an antitumor, T helper 2 response with a suppressed T helper 1 response. Human herpesvirus 8 infection results in a similar immune response supporting the hypothesis that in Tobago, human herpesvirus 8 establishes a chronic infection that can contribute to an immune response favoring the formation and survival of prostate cancer.